Qlone®: A Simple Method to Create 360-Degree Photogrammetry-Based 3-Dimensional Model of Cadaveric Specimens. Issue 6 (18th October 2021) - Gurses, Muhammet Enes; Gungor, Abuzer; Hanalioglu, Sahin; Yaltirik, Cumhur Kaan; Postuk, Hasan Cagri; Berker, Mustafa; Türe, Uğur
Abstract: BACKGROUND: Human cadavers are an essential component of anatomy education. However, access to cadaveric specimens and laboratory facilities is limited in most parts of the world. Hence, new innovative approaches and accessible technologies are much needed to enhance anatomy training. OBJECTIVE: To provide a practical method for 3-dimensional (3D) visualization of cadaveric specimens to maximize the utility of these precious educational materials. METHODS: Embalmed cadaveric specimens (cerebrum, brain stem, and cerebellum) were used. The 3D models of cadaveric specimens were built by merging multiple 2-dimensional photographs. Pictures were taken with standard mobile devices (smartphone and tablet). A photogrammetry program (Qlone®, 2017-2020, EyeCue Vision Technologies Ltd, Yokneam, Israel), an all-in-one 3D scanning and augmented reality technology, was then used to convert the images into an integrated 3D model. RESULTS: High-resolution 360-degree 3D models of the cadaveric specimens were obtained. These models could be rotated and moved freely on different planes, and viewed from different angles with varying magnifications. Advanced editing options and the possibility for export to virtual- or augmented-reality simulation allowed for better visualization. CONCLUSION: This inexpensive, simple, and accessible method for creating 360-degree 3D cadaveric models can enhance training in neuroanatomy and allow for a highly realistic surgical simulation environment for neurosurgeons worldwide.